Mesenchymal Stromal/Stem Cells-Derived Exosomes as an Antimicrobial Weapon for Orodental Infections - Jafari, Nazanin; Khoradmehr, Arezoo; Moghiminasr, Reza; Seyed Habashi, Mina (Frontiers in Microbiology, 2022)
Abstract The oral cavity as the second most various microbial community in the body, contains a broad spectrum of microorganisms which are known as oral microbiome. Oral microbiome includes different types of microbes such as bacteria, fungi, viruses and protozoa. Numerous factors can effect on the equilibrium of oral microbiome community which can eventually lead to orodental infectious diseases. In defending against infection, the immune system has an essential role. Depending on speed and specificity of the reaction, immunity is divided into two different types which named the innate and the adaptive responses but also there is much interaction between them. In these responses different types of immune cells are present including neutrophils, monocytes, macrophages, basophils, dendritic cells, mast cells, eosinophils, and T and B lymphocytes. Recent evidences demonstrate that these cell types both within the innate and adaptive immune systems are capable of secreting some extracellular vesicles named exosomes which are involved in the response to infection. Exosomes are 30–150 nm lipid bilayer vesicles which consist of variant molecules, including proteins, lipids and genetic materials, such as DNA, mRNAs, and regulatory miRNAs and they have been associated with cell-to-cell communications. Exosomes can modulate the innate and specific immune responses of host cells by participating in antigen presentation for activation of immune cells and stimulate the release of inflammatory factors and the expression of immune molecules. On the other hand, exosomes are derived from mesenchymal stromal/stem cells (MSCs) participate in immunomodulation by signaling in target immune cells. Ease of expansion and immunotherapeutic capabilities of MSCs, develop their applications in hundreds of clinical trials. In orodental infectious disease, exosomes can also play an important role by modulating immunoinflammatory responses. Therefore, MSCs-derived exosomes may have potential therapeutic effects to be a choice for controlling and treatment of orodental infectious diseases.